Disseminating Training Courses Information Using SMS - al-Bawaleez, Mahmoud Ahmad Awad (2010)
In these days most media acknowledge the importance of SMS news and web in reaching and interacting with their users. However, there is much discussion regarding the effectiveness when it comes to SMS news. This project to help the students and staff prepared to accept, reading using SMS messages: effective is SMS news compared to traditional news communications. The goal of this study is to investigate the use of SMS news compared to traditional ways distribute in news in different aspects and on the other hand, to develop prototype by using web and SMS technology to apply this system and extent users are willing to accept commercial messages on their mobile phone, since the effectiveness of SMS news highly depends on this willing. The results of this project indicate that the use of the web and SMS for the benefit of disseminating UTLC center training Courses information by extending web technology to SMS using WLAN for students and staff.